YOUTUBE AS LEARNING MEDIA IN STUDENT ENGLISH SPEAKING SKILL IN SMP MUHAMMADIYAH 10 SURABAYA - Vanny Karlina; Waode Hamsia; Ro'ifah (LPPM Universitas PGRI Jombang, 2024)
This study aims to explore how YouTube can be applied as a learning media to improve students' speaking skill at SMP Muhammadiyah 10 Surabaya. The focus is to understand how YouTube can be used to improve speaking skill, addressing specific challenges faced by students in their English learning in speaking. The researcher used a qualitative method as the research design derived from observation and interviews. In addition, the research design was to observe students' activities in the teaching and learning process. The subjects of this study were grade 8 of SMP Muhammadiyah 10 odd semester. The researcher uses of YouTube in speaking learning for 8th grade junior high school students offers significant benefits, such as access to authentic and diverse content and opportunities for independent practice. However, it requires careful supervision and guidance to ensure the quality of content and provide necessary feedback. The result of research showed that the students felt interested in learning English.